A novel method for EMI evaluation in random modulated power electronic converters. (February 2020) - Lezynski, Piotr; Smolenski, Robert; Loschi, Hermes; Thomas, Dave; Moonen, Niek
Graphical abstract: Highlights: Commonly used EMI measuring methods may lead to a wrong assessment of EMI The paper shows the efficient spectrum aggregation method for proper EMI evaluation The method enables selection of resolution and comparison of results Spectrum harmonics are mapped linearly, and the spectrum RMS value does not change. Abstract: However, the theoretical analyses as well as experimental results have indicated that ostensible reduction of the EMI level generated by random modulated converters results from the methodology of the EMI spectrum measurement, adopted in currently binding standards, rather than physical nature of interference generation phenomenon. The experimental investigations, presented in the paper, have shown that utilization of commonly used EMI measuring standards might lead to wrong conclusions in a case of assessment of electromagnetic compatibility of random modulated converters. The aim of this paper is to propose the novel, efficient method enabling objective evaluation of the EMI generated by random modulated converters.